The Complexity of Arabic Learning During the Covid-19 Pandemic at MIN 1 Yogyakarta | Kompleksitas Pembelajaran Bahasa Arab pada Masa Pandemi Covid-19 di MIN 1 Yogyakarta (Masalah, Kurikulum, Keterlibatan Orang Tua) - Mustolikh Khabibul Umam; Rifka Khoirun Nada (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
The realization of Arabic language learning that is generally done face-to-face today must be done online. Not without reason, we realize how the pandemic that began to spread massively led the policy authorities to stop any kind of movement identified with mass social activities. Learning in all institutions from RA/TK level to university level should be discontinued and replaced with online-based learning through internet assistance. This research is categorized as qualitative research and uses data collection techniques in the form of interviews, documentation and analyzed with descriptive analysis strategies. This study is intended to investigate how educational institutions, especially mi education level prepare the arabic learning model applied, researchers want to uncover how the learning steps used by teachers in online-based Arabic learning, student problems during the online learning process and obstacles faced by teachers when the government requires learning to be done online. This research has a purpose direction as a response to the policyholders in overcoming the obstacles of online learning in schools, especially in MIN 1 Yogyakarta. The results obtained in this study are problems faced by educators and students relative to the internal problems of each individual. Educators need to delve deeper into the knowledge of the technology used when learning online, disarming that learners must also focus more on online learning so that the lessons delivered by educators can be absorbed properly. The role of parents is also quite significant in directing and monitoring their children during online learning activities. In addition, the curriculum released by the government in the face of the emergency situation of covid-19 has been quite effective, but in its implementation still requires monitoring and evaluation from policy makers as the initiator of the emergency curriculum.